Quantitative approaches to fiscal sustainability analysis : a new World Bank tool applied to Turkey - Budina, Nina.; Wijnbergen, Sweder van, 1951-; World Bank. Poverty Reduction and Economic Management. Economic Policy and Debt Department ([Washington, D.C.] : World Bank, Poverty Reduction and Economic Management Network, Economic Policy and Debt Dept., 2007)
"Fiscal sustainability analysis (FSA) is an important component of macroeconomic analysis. The authors review various quantitative approaches to FSA with a major objective to bring these approaches together and to present a user-friendly tool for FSA that reflects modern developments. They combine a dynamic simulations approach with a simplified version of the steady-state consistency approach. They also incorporate two different methods to deal with uncertainty: user-defined stress tests and stochastic simulations. The tool goes further by evaluating the required fiscal adjustment as a consequence of the stochastic realizations of the exogenous variables. Furthermore, the fiscal sustainability tool incorporates an endogenous debt feedback rule for the primary surplus, a fiscal policy reaction function. Besides outlining the theoretical framework, the authors also present a case study for Turkey."
"March 2007"--Cover.
Includes bibliographical references (p. 35-37).
Also available in an electronic version.
Keywords: Fiscal policy -- Turkey -- Econometric models; Turkey -- Economic conditions -- Econometric models